Characterization of raw materials and final product in the cement production - Đukić, Duško; Lazić, Dragica; Drljača, Dijana; Imamović, Mugdin (Bulletin of Chemists and Technologists of Bosnia and Herzegovina, 2018)
Cement is a hydraulic binder formed by the grinding process of cement clinker, as intermediate product, which is produced by baking the lime-clay raw material mixture to the sintering temperature. This research paper describes mineralogical analysis technique of primary raw materials, auxiliary components for cement production, by-product clinker  and final product, cement. Used technique is X-ray diffraction technique, which is one of the most modern instrumental techniques today. Obtained results are provided in the form of diffractogram, that is used to display the mineralogical phase of components. X-ray diffraction method confirmed the theoretical knowledge of the mineralogical components of tested raw materials, clinker and cement. As expected, the main component of limestone is mineral calcite, as active compound, fly ash and slag as amorphous substances and clinker contains clinker-minerals and gyspum contains calcium sulfate dihydrate in large percentage. Main components of cement are all minerals provided in clinker and raw materials. These experiments were carried out in the Holding Company Cement Plant in Lukavac, Bosnia and Herzegovina.